Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2021)
A dataset containing 1037217 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is one of (Gadiformes)", "HasCoordinate is true" ] } The dataset includes 1037217 records from 498 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0181897-200613084148143/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences